2008
DOI: 10.1590/s1413-78522008000400007
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura do terço distal da perna com retalhos de perfurantes pediculados

Abstract: Os retalhos de vasos perfurantes representam um avanço no tratamento das perdas cutâneas. No terço distal da perna as opções para a cobertura cutânea são poucas e muitas vezes devemos recorrer a microcirurgia. Neste trabalho realizou-se uma avaliação prospectiva de 20 pacientes submetidos ao tratamento de áreas cruentas no terço distal da perna através de retalhos pediculados em artéria perfurante. A localização das artéria perfurantes foi feita , no pré-operatório , através do exame de eco-doppler. Os retalho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
8
0
3
Order By: Relevance
“…However, microsurgical techniques require specialized training and in most hospitals there are no specialists available to carry them out. In addition, such patients usually require additional operations to [5][6][7] . The gastrocnemius and soleus muscles, being vascularized predominantly in their proximal regions, allow the rotation about the axis of the pedicle (good arc of rotation), without compromising vitality.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…However, microsurgical techniques require specialized training and in most hospitals there are no specialists available to carry them out. In addition, such patients usually require additional operations to [5][6][7] . The gastrocnemius and soleus muscles, being vascularized predominantly in their proximal regions, allow the rotation about the axis of the pedicle (good arc of rotation), without compromising vitality.…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…5 When assessing the profile of individuals involved in motorcycle accidents in the city of São Paulo, Brazil, Debieux et al 15 observed that most injuries occurred in the lower limbs (53.9%), and more frequently in the age group between 21 and 24 years (45%). Rezende et al, 9 when evaluating the epidemiological profile, surgical treatment and postoperative results of patients with complex traumatic injuries to the lower limbs, observed that the motorcycle accident was responsible for the majority of the injuries (37.8%), and that the lower third of the leg was the region most affected by trauma (50.4%), followed by the medial third (32%).…”
Section: Discussionmentioning
confidence: 99%
“…The factors involved in choosing the most appropriate surgical technique include the location, the extent of the lesion, the exposure of noble structures, and the surgeon's experience with reconstruction techniques. 9 The use of the propeller flap to cover lesions is an option when the area to be treated is small to medium in size, located in a well-vascularized region, and surrounded by healthy tissues. In this technique, we should consider the quality and volume of the transferred soft tissue, the orientation of the scar and the adequate planning of the flap, to enable the direct closure of the donor site without tension in the area.…”
Section: Introductionmentioning
confidence: 99%
“…In this segment, there is no interposition of the muscular tissues between the noble structures and integument; thus, it has limited distensibility and mobility. Therefore, the use of skin grafts and random rotation flaps is inadequate for wounds that affect the full thickness of the skin 10 . In these cases, it is necessary to use distant flaps, which can be fasciocutaneous or free 11 .…”
Section: Discussionmentioning
confidence: 99%